2021
DOI: 10.3389/fped.2020.556805
|View full text |Cite
|
Sign up to set email alerts
|

Use of Audiobooks as an Environmental Distractor to Decrease State Anxiety in Children Waiting in the Pediatric Emergency Department: A Pilot and Feasibility Study

Abstract: Objectives: Anxiety and anticipatory stressors are commonly experienced by children visiting the Pediatric Emergency Department (PED), but little research exists that addresses the efficacy of interventions to decrease this stress. This one-sample pretest-postest pilot study gathered preliminary data on the feasibility and effectiveness of utilizing audiobooks to reduce fear and state anxiety in children in the PED.Methods: Participants were 131 children in kindergarten through 8th grade (M = 9.4 years, 54% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…This emphasizes the importance of being attuned to a variety of psychosocial needs that children have when they present for medical care. Interestingly, a small study has previously found that audiobooks can reduce fear and anxiety for children in ED waiting rooms [ 15 ]. Other small studies of child satisfaction in the ED have focused on more general information needs and pain management [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the importance of being attuned to a variety of psychosocial needs that children have when they present for medical care. Interestingly, a small study has previously found that audiobooks can reduce fear and anxiety for children in ED waiting rooms [ 15 ]. Other small studies of child satisfaction in the ED have focused on more general information needs and pain management [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%